Ufa State Aviation Technical University: realities and prospects of its transformation into a world-class innovation university - Криони N. K.; Алеxандров I. V. (Materials. Technologies. Design, 2019)
Looks at the main activities of Ufa State Aviation Technical University, its best experience and achievements. It draws upon the university’s potential, its contribution to training, research and innovation. Particular attention is paid to specific measures aimed to strengthen ties with the industry and practical orientation of student education. The article defines the university strategic vision for education developing and focuses on research areas. Its core goal is stated: to transform Ufa State Aviation Technical University into an innovative University 4.0.